'Effects of novel root repair materials on attachment and morphological behaviour of periodontal ligament fibroblasts: Scanning electron microscopy observation'. Issue 12 (20th September 2016) - Akbulut, Makbule Bilge; Uyar Arpaci, Pembegul; Unverdi Eldeniz, Ayce
Abstract: The aim of this study was to evaluate the adhesion of periodontal ligament fibroblasts (PDLs) on newly proposed root repair materials [Biodentine, MM‐MTA, polymethylmethacrylate (PMMA) bone cement, and SDR], in comparison with contemporary root repair materials [IRM, Dyract compomer, ProRoot MTA (PMTA), and Vitrebond]. Five discs from each material were fabricated in sterile Teflon molds, and the specimens were aged and prewetted in cell culture media for 96 hours. Three material discs were used for scanning electron microscopy (SEM) for the assessment of the attachment, density, and morphological changes in the PDLs, while two samples were used for energy dispersive x‐ray spectroscopy (SEM‐EDX) to determine the elemental composition of the materials. Human PDLs were plated onto the materials at a density of 10, 000/well, and incubated for 3 days. The SEM micrographs were taken at different magnifications (500× and 5000×). In the SEM, the cells were attached and well spread‐out on the surfaces of the Biodentine, PMTA, and Dyract compomer, while varied cell densities and morphological alterations were observed in the Vitrebond, IRM, MM‐MTA, SDR, and PMMA bone cement groups. The SEM‐EDX analysis revealed a maximum calcium percentage in the PMTA specimens, as well a maximum silicon percentage in the Dyract compomer specimens. This in vitro study demonstrated that the Biodentine and Dyract compomer supported PDL cell adhesion and spreading. The PMTA presented a favorable scaffold for better attachment of the PDL cell aggregates. Therefore, the calcium and silicon content of a material may enhance the PDL cell attachment.